Stigma and labelling of immigrant personal support workers during COVID-19 pandemic in Ontario: Implications for policy - Quinn Talbot; Evans Batung; Isma Yusuf; Francisca Omorodion; Godwin Arku; Isaac Luginaah (PLoS ONE, 2026)
The COVID-19 pandemic had a profound impact on the livelihoods of people from diverse socio-economic backgrounds in Canada. In this study, we focus on immigrant essential workers, who played pivotal roles in sustaining Canada’s socio-economic and healthcare sectors during this crisis. Drawing data from twenty-five in-depth interviews with immigrant personal support workers, we found that immigrant personal support workers experience a complex and compounding type of stigma, traceable to their location at race, gender, class, and ethno-national lines. Using intersectionality and stigma as guiding theoretical frameworks, our study looks at the impact of stigma and labelling on personal support workers in the Windsor, Ontario, Canada, the intersectional character of such stigma, and the novel challenges introduced by the pandemic. The findings show that although some people praised personal support workers for their work on the frontlines, since others viewed them as carriers of the COVID-19 virus, certain changes had to be made to their daily routines to avoid being seen as a personal support worker. Additionally, challenges in the workplace included lack of personal protective equipment and unsafe work environments. Immigrant personal support workers were affectionately labelled ‘essential’ workers, as they were performing critical tasks at the forefront of the pandemic response. Personal support workers also found themselves in a duality of public opinion by being recognized as ‘essential’ workers, yet being simultaneously stigmatized as potential sources for the spread of COVID-19. The findings provide insights into changes that need to be made in the future toward improving immigrant personal support workers’ health and well-being in times of crises.